2005
DOI: 10.1037/0022-006x.73.5.972
|View full text |Cite
|
Sign up to set email alerts
|

Mediated paths to overreactive discipline: Mothers' experienced emotion, appraisals, and physiological responses.

Abstract: The present investigation was designed to evaluate whether mothers' emotion experience, autonomic reactivity, and negatively biased appraisals of their toddlers' behavior and toddlers' rates of misbehavior predicted over-reactive discipline in a mediated fashion. Ninety-three community mother-toddler dyads were observed in a laboratory interaction, after which mothers' emotion experience and appraisals of their toddler's behavior were measured via a video-recall procedure. Autonomic physiology and over-reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
140
3
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(157 citation statements)
references
References 58 publications
12
140
3
2
Order By: Relevance
“…For example, both trait anger (e.g., Wilkowski, Robinson, Gordon, & TroopGordon, 2007;Wingrove & Bond, 2005), and reactive aggression have been linked to hostile attribution biases (Crick & Dodge, 1994;Dodge & Coie, 1987). Lorber and O'Leary (2005) lend support to the notion that cognition may mediate the impact of negative affect on behavior. Their interactive laboratory paradigm examined the role of emotion in parenting for mothers of preschool aged toddlers.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…For example, both trait anger (e.g., Wilkowski, Robinson, Gordon, & TroopGordon, 2007;Wingrove & Bond, 2005), and reactive aggression have been linked to hostile attribution biases (Crick & Dodge, 1994;Dodge & Coie, 1987). Lorber and O'Leary (2005) lend support to the notion that cognition may mediate the impact of negative affect on behavior. Their interactive laboratory paradigm examined the role of emotion in parenting for mothers of preschool aged toddlers.…”
Section: Discussionmentioning
confidence: 80%
“…Their interactive laboratory paradigm examined the role of emotion in parenting for mothers of preschool aged toddlers. When parent report of moment-to-moment negative emotion was considered, modeling indicated a pathway whereby child misbehavior led to parent negative emotion, which resulted in parent negative appraisal biases and, as a consequence, parent overreactivity (Lorber & O'Leary, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Noting its inconsistent conceptualization in the parenting literature, we define parenting stress as the perception of the parenting role as overwhelming, consistent with psychological theories of stress that emphasize the appraisal of environmental circumstances as beyond one's coping resources (Cohen, Gianaros, & Manuck, 2016). Stress is strongly associated with the experience of negative emotion and increases in cardiovascular activity (Cohen et al, 2000), each of which is implicated in CPUN and/or harsh discipline (e.g., Leung & Slep, 2006;Lorber & O'Leary, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining parenting style and disciplines have found that poorer emotion regulation strategies (such as suppression and reappraisal) (Lorber & O'leary, 2005) and greater negative emotional arousal in parenting tasks (measured with self-report as well as with physiological measures) are linked with over-reactive discipline (Lorber & O'leary, 2005) .…”
Section: Discussionmentioning
confidence: 99%